Commentary on: ‘Pacifiers Use in Term Infants and Breastfeeding: Caution with the Cochrane Results’ - Binns, Colin; Lee, S. (John Wiley & Sons Ltd, 2013)
This is a commentary of Cochrane review, published in this issue of EBCH, first published as: Jaafar SH, Jahanfar S, Angolkar M, Ho JJ. Pacifier use versus no pacifier use in breastfeeding term infants for increasing duration of breastfeeding. Cochrane Database of Systematic Reviews 2011, Issue 3. Art. No.: CD007202. DOI: 10.1002/14651858.CD007202.pub2.